Use of Granulocyte Colony-Stimulating Factor Among Patients of Chronic Liver Disease in a Tertiary Hospital in Nepal: A Pilot Study - Pathak, Rahul; Thapaliya, Sabin (Medical Journal of Shree Birendra Hospital, 2019)
Introduction: Granulocyte colony stimulating factor improves short-term survival and clinical outcomes in alcoholic hepatitis, acute-on-chronic liver failure and decompensated chronic liver disease. Our study aimed to assess survival benefit and change in Child-Turcotte-Pugh and Model For End-Stage Liver Disease scores 30 days after Granulocyte colony stimulating factor therapy in chronic liver disease patients, irrespective of their mode of presentation. Methods: This was a prospective observational study conducted in a university teaching hospital, where 25 patients with chronic liver disease were given 300 micrograms of Granulocyte colony stimulating factor subcutaneously 12 hourly plus standard medical therapy. We assessed survival until day 30. Child-Turcotte- Pugh and Model For End-Stage Liver Disease scores at enrolment and 30 days after treatment were compared. Results: 21 of 25 patients treated with Granulocyte colony stimulating factor survived at day 30. Treatment with Granulocyte colony stimulating factor reduced Child-Turcotte-Pugh score from 10.33 ± 1.24 to 8.76 ± 1.79 (p< 0.001) at day 30 and Model For End-Stage Liver Disease score from 22.10 ± 4.67 to 16.38 ± 5.52 (p < 0.001) at day 30. Conclusions: Granulocyte colony stimulating factor improves clinical outcome, Child-Turcotte-Pugh and Model For End-Stage Liver Disease scores in patients admitted with chronic liver disease for any cause. Further studies are needed to explore whether lower doses (total six doses) of Granulocyte colony stimulating factor are as effective as higher doses (total 10 doses).